CUTICULAR COMPONENT ANALYSIS FOR DISCRIMINATION OF AEDES AEGYPTI (LINNAEUS) FROM BANJARMASIN AND YOGYAKARTA - Abdul Gafur (Bioscientiae, 2004)
Gas chromatographic analysis of cuticular component was carried out to reveal differences in cuticular hydrocarbon composition among populations of Aedes aegypti that are spatially far separated. Females from two populations in Banjarmasin and one in Yogyakarta were compared. Stepwise discriminant analysis selected five discriminator peaks from chromatograms, which, by cross validation, could be used to distinguish between females of the three populations with 100% success rate. This indicates genetic differences between populations of Aedes aegypti in Banjarmasin and that in Yogyakarta.